Hubungan Mutu Pelayanan dengan Kepuasan Pelanggan Batik (Studi Kasus di Quina Batik) - Agung Hartadi; Ika Tirta Candra Rini (Jurnal Bisnis, Manajemen, dan Akuntansi, 2022)
This research to see the relationship between Service Quality and Customer Satisfaction with batik, a case study at Quina Batik. Where the research subjects are customers at Quina Batik with a total of 100 customers. By taking samples through total sampling technique. Data was collected using a Likert scale consisting of two scales, namely the Service Quality scale and the Customer Satisfaction scale. The data analysis method used is Product Moment Analysis. The result is that there is a significant positive relationship between Service Quality and Batik Customer Satisfaction at Quina Batik. Service quality has an effect on customer satisfaction of 71.7%. This means that there are still 28.3% of the influence of other factors on customer satisfaction. From these results, it is hoped that Quina Batik will improve its ability to provide everything that its customers expect or in other words, whether or not the quality of service is good depends on the ability to provide services to consistently meet customer expectations. Keywords: Service Quality; Customer Satisfaction;Quina Batik.